University teachers' beliefs and constructivist teaching practices in blended learning courses in Tanzanian universities. (2018) - Machumu, Haruni; Zhu, Chang; DePryck, Koen
The study examines the relationship between university teacher's beliefs and constructivist teaching practices (CTP) in blended learning environment (BLE) courses in Tanzanian universities. The study collects data from 211 teachers in BLE courses. The analyses involved descriptive statistics, correlational, the Mann-Whitney U-test, Kruskal-Wallis H-test and multiple linear regression. The findings revealed threefold. First, explicit engagement, supportive teaching and interactions were important aspects of CTP in BLE courses. Second, there were no statistically significant differences in teachers' beliefs about gender, academic rank, educational level and teaching experiences in BLE courses. And, third, there was a significant relationship between teachers' beliefs and CTP in BLE courses. Moreover, the findings indicate that teachers' beliefs predict their explicit engagement and supportive teaching are predictors of the beliefs of teachers who teach BLE courses. This study provides important implications and empirical evidence about the beliefs of the university teachers who teach BLE courses and their CTP.